2020
DOI: 10.3389/fvets.2020.00547
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Treatment Practices of Equine Endometritis—A Questionnaire

Abstract: Endometritis is a major cause for impaired fertility in mares. The objectives of this study were to collect information on diagnostic and treatment practices performed by veterinarians and to investigate possible effects of professional experience, caseload, and geographical location on the practitioners' management of endometritis cases. For this purpose, equine practitioners ( n = 680) were asked to fill out an online survey (34 questions). The online survey yielded 117 responses by ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…However, mares that fail to properly evoke such systemic inflammatory reaction are more likely to be susceptible for endometritis [ 21 , 24 ]. Endometritis provides the uterine environment with unsuitable conditions for sperm cells and implantation of the embryo [ 25 ]. In the last decades, there were several attempts to properly trace and control the pathophysiological pattern of equine endometritis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mares that fail to properly evoke such systemic inflammatory reaction are more likely to be susceptible for endometritis [ 21 , 24 ]. Endometritis provides the uterine environment with unsuitable conditions for sperm cells and implantation of the embryo [ 25 ]. In the last decades, there were several attempts to properly trace and control the pathophysiological pattern of equine endometritis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers conducted very promising prognostic and diagnostic techniques for endometritis in mares, which precisely help in the management of such crucial conditions. These techniques were mainly explored through checking various cytological, microbiological, ultrasonographical and serological biomarkers in mares suffering from endometritis [ 25 – 27 ]. However, these different methodologies did not achieve better understanding of molecular regulation of equine endometritis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of a variety of treatment options ( Table 1 ), evidence-based reports on their effectiveness are lacking ( 66 ). A recent survey of equine practitioners in Germany concluded that most still mainly use systemic antibiotic therapy for equine endometritis ( 67 ). Slightly less than one half of respondents used uterine lavage in addition to the systemic antibiotics.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…For uterine lavages, practitioners had mostly changed to 0.9% saline instead of potentially more irritant substances such as povidone iodine, N-acetylcysteine, hydrogen peroxide, dimethyl sulfoxide, or kerosene. Köhne et al ( 67 ) called for more research and better dissemination of results to clinicians in an effort to provide effective treatment.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…[38][39][40] The use of endometrial biopsy as part of the breeding soundness exam is no longer considered routine by many equine clinicians and theriogenologists, and is now reserved as an additional test when other, less-invasive tests, such as transrectal palpation, ultrasonography, uterine cytology, and uterine bacterial culture, have already been done. 20,21,36 Given the continuous evolution of minimally contaminated breeding techniques and new uterine therapies, foaling rates are continuing to improve, specifically for biopsies within the 2 middle categories. Therefore, less emphasis is being placed on the foaling rates originally proposed by Kenney and Doig, and overall categorization of biopsies has become less important in the theriogenology world, in which theriogenologists are now trained to read their own biopsies.…”
mentioning
confidence: 99%